Merdeka Belajar-Kampus Merdeka - Fahmi, Santri; Sinaga, Rizky Awaliyah; Fitriani; Dalimunthe, Jelita; Darlis, Ahmad (Ikatan Dai Indonesia, 2023)
Education is a way of endeavor for every human being to seek a decent life to continue life in an increasingly advanced and developing era. Discussion related to education in the State of Indonesia, has been contained in Law no. 20 of 2003. In order to achieve the target of education, it is necessary to have a curriculum to assist and facilitate the educational process. The Minister of Education and Culture or Nadim Makarim has initiated a new curriculum called MBKM (Freedom Learning Campus Merdeka). The Independent Learning Curriculum has the goal of liberating education by liberating ways of thinking and liberating new innovations. Socialization related to the Merdeka Learning Campus Merdeka program is also often carried out to be able to understand the concept of this curriculum. Understanding of Freedom to Learn on an Independent Campus needs to be deepened so that it can be realized as much as possible. Merdeka Learning Campus Learning is a program from the Minister of Education and Culture with the main vision of supporting students to have various abilities and understanding of various knowledge so that they are ready to be involved in the world of work. Permendikbud Number 3 of 2020 has explained regarding the National Higher Education Standards which discuss the MBKM policy. In some views, Merdeka Learning provides an opportunity for students to learn individually or independently and be responsible for themselves. Students are allowed to participate in the learning process that is carried out outside of their department on campus or other campuses in several types of activities. The participation of students in these activities has many positive values ​​and can provide learning experiences to prepare them for facing life in the future. In order for this learning experience to materialize, it is hoped that good cooperation between universities and the industrial/business world and the government is expected. The collaboration was initiated within the framework of developing the professionalism of the academic community. The study in this research uses a literature study approach which has the possibility of providing reference material in other research to serve as a basis for research related to MBKM.